Kinerja Inverter 500 W untuk PLTS Skala Kecil - Slamet Nurhadi; Muhammad Fahmi Hakim; Ferdian Ronilaya; Sukamdi; Rahmania Putri Yulissa (Politeknik Negeri Malang, 2024)
At Electrical Engineering Department of Politeknik Negeri Malang, there is an EBT learning module in the form of solar panel with small capacity, namely 80 Watts. The only load that can be supplied is DC load because there isn’t installed inverter. Therefore, it is necessary to determine the inverter specifications to be installed in small-scale solar system. This research aims to determine the specifications and test the performance of a 500 W inverter integrated with a 50 Wp solar system. Also analyze power quality parameters and efficiency when connected to various load. The test method is no-load and load testing with the parameters measured including current, voltage, power, frequency and THD. Analysis was also carried out on the correlation between efficiency and loading and inverter pins with THDV and THDI. In the no-load test, the inverter output voltage waveform was obtained as a pure sine wave with a frequency of 50.10 Hz. In testing the LED and LHE loads, it was found that the inverter was good for use when the load was 50-80% of its capacity. The lowest THDV value is at a Pin value of 26 W, namely a THDV value of 0.009%. The highest THDV on the Pin is 130 W with THDV value of 1.9%. The lowest THDI value is at Pin 9.75 W, namely 27.6%. The highest THDI value on the 130 W Pin is 80.9%. The THD limit is still within the IEEE standard limit, namely 5% - 10%.